(untitled) (Fiep Bulletin - online, 2016)
In our thesis we compared the successfulness of technical-tactical activities in Wrestling Freestyle of men and women at the World Championships in 2013. Our group consisted of wrestlers with an average age of 25,73 (± 3,65), average height 173, 88 (± 9,92) cm and active practice of 14,39 (± 4,49) years and women wrestlers with an average age of 24,52 (± 3,48), average height of 163 (± 7,11) cm and the average active practice of 11,88 (± 5,17) years. The results were obtained by using a detailed video analysis, where we watched 126 matches of which 63 were women matches and 63 men matches in seven weight categories. During evaluating obtained data we used relational analysis chi-square to find out relation between used technical-tactical activities by men and by women. In the monitored technical-tactical activities we found out a statistically significant difference in the number of successful , double-leg attack“ in favor of men (x2 = 3,99; p ? 0,05). In other monitored technical-tactical activities were not seen significant differences.